Green Synthesis dan Karakterisasi Nanopartikel Emas Sebagai Antioksidan Peredam Radikal Bebas - Denok Risky Ayu Paramita; Hadi Barru Hakam Fajar Siddiq; Roisa Zakia Zahra Lasmono (Fakultas Teknik Universitas Wahid Hasyim, 2026)
Gold nanoparticles (AuNPs) have significant potential in healthcare due to their antioxidant activity. However, conventional physical and chemical synthesis methods are costly and generate hazardous waste. Green synthesis offers a more economical and environmentally friendly alternative. In this study, katuk leaf extract was used for the first time as a reducing agent in the green synthesis of AuNPs, owing to its rich phenolic content. The aim of this research was to synthesize and characterize AuNPs using katuk leaf extract and to evaluate their antioxidant activity against free radicals. UV–Vis spectrophotometry showed an optimum wavelength at 530 nm, indicating the formation of wine-red AuNPs. SEM analysis revealed spherical particles with sizes ranging from 28 to >100 nm. XRD results, based on JCPDS No. 04-0784, confirmed a face-centered cubic (FCC) crystalline structure with Bragg reflections at 2θ values of 38.03°, 44.15°, 64.25°, and 77.25°, corresponding to (111), (200), (220), and (311) planes. DPPH analysis yielded an IC₅₀ value of 53.37, indicating strong antioxidant activity and potential applications in the health sector.